Features of the Formation of Guilloche Rosettes (Journal of Universal Science Research, 2023)
Geometric structures play an important role in exploring and studying the world around us. These designs are present both in nature and in technical solutions implemented by man. At the same time, these structures help influence various processes that are important to humans. One of the tools for implementing such designs and their implementation in various areas of cognition is guilloche. At the same time, the construction of guilloche is largely determined by the area of its application. Based on this, the work pays special attention to the peculiarities of the formation of guilloche rosettes.